Baseball resistance training: Should power clean variations be incorporated? - Suchomel, T. J.; Sato, K. (Journal of Athletic Enhancement, 2013)
The power clean and its variations are prescribed by many collegiate and professional strength and conditioning coaches in order to train lower body muscular power. Lower body muscular power is an essential component to the overall performance of athletes in their respective sports. Although baseball is a sport that requires lower body power to be successful, it has not followed the trend of other sports that use Olympic lifts and their variations to train lower body power. Speculation leads practitioners to believe that baseball players consider Olympic lifts to be harmful to their shoulders and wrists because of the traditional over-head catch position of the snatch and jerk and the catch position of the power clean respectively. There are several power clean variations that produce high amounts of lower body power and may decrease the chance for injury to the shoulders and wrists. The high pull, jump shrug, and mid-thigh pull are three power clean variations that are used in the teaching progression of the power clean. Previous research indicated that the high pull, jump shrug, and mid-thigh pull can produce high amounts of lower body power that may be superior to a power clean variation that includes the catch phase. Because of the simplistic nature of these variations, it is likely the chance of injury to the shoulders and wrists will decrease.